Adverse cardiovascular effect following gonadotropin-releasing hormone antagonist versus GnRH agonist for prostate cancer treatment: A systematic review and meta-analysis - Li Gu; Xurui Li; Wentao Liu (Frontiers in Endocrinology, 2023)
BackgroundAndrogen deprivation therapy is the mainstay of medical treatment for prostate cancer (Pca); however, it is associated with an increased risk of adverse cardiovascular (CV) events and death. To date, CV death has been the leading noncancer cause of death in Pca patients. Both GnRH antagonists (an emerging class of drugs) and GnRH agonists (most frequently prescribed) are efficacious against Pca. However, the adverse effects, especially the adverse CV effect between them remain unclear.MethodsThrough a literature search using MEDLINE, EMBASE and the Cochrane Library, all available studies comparing the safety of CV risk between GnRH antagonists and GnRH agonists in Pca patients were extracted. Comparisons of outcomes of interest between these two classes of drugs were calculated using the risk ratio (RR). Subgroup analyses were performed depending on the study design and preexisting CV disease at baseline.ResultsNine randomized controlled clinical trials (RCTs) and five real-world observational studies comprising 62160 Pca patients were included in our meta-analysis. Patients receiving GnRH antagonists experienced fewer CV events (RR: 0.66, 95% CI:0.53-0.82, P<0.001), CV death (RR:0.4, 95% CI: 0.24-0.67, P<0.001) and myocardial infarctions (RR: 0.71, 95% CI: 0.52-0.96, P=0.03). No difference was found in the incidence of stroke and heart failure. Moreover, GnRH antagonists were associated with fewer CV events in patients with preexisting CV disease but not in those without preexisting CV disease in the RCT series.ConclusionGnRH antagonists appear to offer favorable safety in terms of adverse CV events and CV death compared with GnRH agonists among men diagnosed with Pca, especially those who had established CV disease at baseline.Systematic review registrationhttps://inplasy.com/inplasy-2023-2-0009/, identifier INPLASY202320009.